The Kshetteli Language: Sociolinguistic and Linguistic Situation & Some Strategies for Its Preservation - Regmi, Dan Raj (Journal of Jayaprithvi Multiple Campus, 2025)
This paper briefly introduces the current sociolinguistic and linguistic situation of the Kshetteli language and suggests some strategies for its preservation. Kshetteli, a Tibeto-Burman language, is spoken by only four speakers residing in Jhusku, Salli and Khatti villages of Apihimal Rural Municipality of Darchula district of Nepal. This language, which was recently discovered, is used merely in the limited domains of language use. Only some sociolinguistic and linguistic features (viz. some vocabularies and grammatical features) of the language have been scantily recorded by personal and institutional efforts. Named after the Kshetti village, it was exclusively spoken by Bohara in the bygone days. Later, it was spoken as a common tongue by Bohara, Dhami, Rokaya, Manyal and Atyal. Now-a-days, Kshetteli has been considered as one of backbones of identity of the municipality as well. Many linguistic features have been lost and shifted to Nepali or other local dominant language. Sociolinguistically, this is a critically endangered language (viz., vitality level 8b) as it is spoken by only the people of grandparent generation. Thus, appropriate to the current vitality level, some community-based language development strategies like identification and restoration of historical links, top-down and down-up integration, language revitalization, radio programs and mother/child language programs and establishment of language learning center including the local language policy need to be developed in collaboration of local government, community, community organizations, experts and national and international agencies immediately for its preservation.